Art in Emerson and Dewey: theoretical and practical propositions for pedagogy (Revista Apotheke, 2024)
This article analyzes aspects of the conceptualization elaborated by the philosopher and educator John Dewey (1859-1952) and by the essayist and poet Ralph Waldo Emerson (1803-1882) about art. Without intending to analyze all the complexity involved in this theme, the article aims to offer theoretical subsidies and practical alternatives for pedagogical work with the arts. The first two sections discuss the theses of each of these authors on the topic under analysis, and the third presents a fictional narrative about the experiences of a preschool teacher with teaching arts. The final section discusses this peculiar exposure mode, which combines theoretical treatment with the report of an imaginary situation, highlighting that its objective is to encourage teachers to develop creative teaching procedures, as opposed to the dehumanizing tendencies that are now introduced into education.
Keywords: John Dewey; Ralph Waldo Emerson; art; contemporary education